A currency board for European Monetary Union outsiders - Matthias Sutter (Intereconomics, 1996)
It is becoming clear that strict interpretation of the Maastricht criteria and adherence to the 1.1.1999 as the starting date for EMU will lead to a two-speed monetary union with insiders and outsiders. In this case, the author proposes the introduction of a currency board for outsiders in order to ensure a minimum of convergence before these countries join EMU as well as to confront the danger that outsiders may become faced with longer term obstacles to membership. *** DIRECT SUPPORT *** A02GP105 00003
Keywords: 330; European Monetary Union